Le regard mélancolique dans la poésie de Baudelaire (TEST Ticontre. Theory Text Translation, 2018)
Eyes deprived of sight are a recurring oxymoron in Les Fleurs du mal. As a figure which bundles a variety of phenomena, from pure appearance to the seductive regard of the commodity, it can be read as an allegory of modern Eros. This article intends to examine the figure in the light of W. Benjamin’s reflexion on Baudelaire. The eyes deprived of sight relate to a Renaissance concept, Melanchthon’s “melancholia illa heroica”, as well as to destruction of the aura understood as a heroic affirmation of mechanical reproduction. Parting from this historical construction, Baudelaire’s figure of the eyes deprived of sight seems to move towards a double issue. In one case, the metamorphosis of empathy through the mediation of critical melancholy, option detailed in this article. In the other case, an erotic affirmation of mechanical reproduction which abandons melancholy without leaving the sphere of redemption.
Keywords: Baudelaire; Benjamin; melancholic Eros; allegory; dialectical image; Prostitute; empathy with the commodity